2009
DOI: 10.1037/a0016978
|View full text |Cite
|
Sign up to set email alerts
|

Bringing meaning to numbers: The impact of evaluative categories on decisions.

Abstract: Decision makers are often quite poor at using numeric information in decisions. The results of 4 experiments demonstrate that a manipulation of evaluative meaning (i.e., the extent to which an attribute can be mapped onto a good/bad scale; this manipulation is accomplished through the addition of visual boundary lines and evaluative labels to a graphical format) has a robust influence in health judgments and choices and across diverse adult populations. The manipulation resulted in greater use of numeric quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(205 citation statements)
references
References 55 publications
9
195
0
1
Order By: Relevance
“…[125][126][127] Findings broadly indicate that comprehension of the information is improved, particularly for people with low numeracy. 128 Furthermore, the same study suggested that evaluative categories can increase deliberative processing of the numerical information. Numerical descriptors may also increase perceptions of risk and, as a result, may be more effective at altering behaviour than numerical information in isolation.…”
Section: Numerical Informationmentioning
confidence: 99%
“…[125][126][127] Findings broadly indicate that comprehension of the information is improved, particularly for people with low numeracy. 128 Furthermore, the same study suggested that evaluative categories can increase deliberative processing of the numerical information. Numerical descriptors may also increase perceptions of risk and, as a result, may be more effective at altering behaviour than numerical information in isolation.…”
Section: Numerical Informationmentioning
confidence: 99%
“…There were several studies conducted to test the associations of numeracy and the understanding and the use of numeric information in risk and health domains (e.g., Hibbard, Peters, Dixon, & Tusler, 2007;Lipkus et al, 2001;Nelson, Fagerlin, Lipkus, & Peters, 2008;Peters, 2008;Peters et al, 2009;Peters, Hibbard, Slovic, & Dieckman, 2007;Peters & Levin, 2008;Woloshin, Schwartz, Black & Welch, 1999). Sheridan and Pignone (2002) investigated medical students' numeracy level, and its association to the 8 ability to interpret risk infom1ation.…”
Section: Previous Findings: Influence Of Numeracy On Judgments and Dementioning
confidence: 99%
“…Because participants were able to evaluate how good a 20,000-word entry was compared to a 10,000-word entry and, arguably, word entry was more important factor than the cosmetics of the dictionary, they were willing to pay more for the dictionary with a 20,000-word entry. Peters et al (2009) manipulated "evaluability" by providing affective labeling to numeric ratings. They presented pmiicipants with hard-to-evaluate healthcare ratings (e.g., score of 93 out of 100 for a survival rate), and provided affective categories (e.g., good, poor) to help the healthcare ratings become more "evaluable."…”
Section: Previous Findings: Influence Of Numeracy On Judgments and Dementioning
confidence: 99%
“…Choice architecture can be applied in multiple ways and in a variety of application scenarios (see Table 1 in the Appendix for applications to support environmental conservation behavior) [50], [54]- [66]. Nudging towards environmental conservation behavior, for instance, can take the form of placing consumptiondependent emoticons on energy bills -or information about one's own and the neighbors' average consumption.…”
Section: Overcoming Innovation Resistance With Choice Architecturementioning
confidence: 99%